2020
DOI: 10.1371/journal.pone.0242371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quantified dry cupping on soft tissue compliance in athletes with myofascial pain syndrome

Abstract: Purpose This study aimed to develop a quantitative dry cupping system that can monitor negative pressure attenuation and soft tissue pull-up during cupping to quantify soft tissue compliance. Methods Baseball players with myofascial pain syndrome were recruited to validate the benefits of cupping therapy. Nine of 40 baseball players on the same team were diagnosed with trapezius myofascial pain syndrome; another nine players from the same team were recruited as controls. All participants received cupping wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…found that a cupping intervention effectively improved soft tissue compliance, shoulder, and upper limb functions in baseball players. 78 A recent study also found that cupping therapy could reduce inflammation after strenuous exercises. Ekrami et al.…”
Section: Cuppingmentioning
confidence: 96%
“…found that a cupping intervention effectively improved soft tissue compliance, shoulder, and upper limb functions in baseball players. 78 A recent study also found that cupping therapy could reduce inflammation after strenuous exercises. Ekrami et al.…”
Section: Cuppingmentioning
confidence: 96%
“…Recent research starts to investigate the biomechanical responses of muscles after applying cupping therapy, and the efficacy of cupping therapy on treating musculoskeletal conditions (Chiu et al, 2020;Jan et al, 2021). For example, cupping therapy with a negative pressure of 400 mmHg for 15 min each time, twice a week, for 4 weeks can be used to improve functional recovery and health in athletes with trapezius myofascial pain syndrome (Chiu et al, 2020). One of the benefits of cupping therapy is considered to be the reduction of muscle stiffness (Jan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cupping therapy is easier to apply compared to massage and stretching that require extensive training of a clinician. Recent research starts to investigate the biomechanical responses of muscles after applying cupping therapy, and the efficacy of cupping therapy on treating musculoskeletal conditions ( Chiu et al, 2020 ; Jan et al, 2021 ). For example, cupping therapy with a negative pressure of 400 mmHg for 15 min each time, twice a week, for 4 weeks can be used to improve functional recovery and health in athletes with trapezius myofascial pain syndrome ( Chiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, wet cupping involves prior incisions to the superficial skin, which will be followed by cups suction for bloodletting (Al Bedah, et al, 2016;Stephens, Selkow, & Hoffman, 2020;Wang, et al, 2020). Recently, cupping treatment has become more popular in athletic populations as a sports medicine treatment for musculoskeletal disorders, and purportedly for enhancing recovery and maximal effort performance (Bridgett, Klose, Duffield, Mydock, & Lauche, 2018;Cao, Li, & Liu, 2012;Chiu, Manousakas, Kuo, Shiao, & Chen, 2020;Ekrami, Ahmadian, Nourshahi, & Shakouri, 2021). Despite the use of cupping by some athletes in the 2016 Rio Olympics and other sports events, there has been limited evidence to support its efficacy in improving the high intensity exercise performance (Bridgett, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%